Analisis Perbandingan Rencana Anggaran Biaya (Rab) Bangunan Menggunakan Metode Sni dan Bow - Jamrud, Faris; Hi.Muhammad, Amiruddin; Altarans, Indra (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research compares cost estimations between SNI and BOW methods for the Lelilef Health Center construction project in Central Halmahera. The study was motivated by health service urgencies in the mining area, a large project scale (Rp 7,929,854,690.00), mixed funding (DAK + CSR), and implementation challenges (delayed worker payments). The research aims to determine the cost estimations using SNI and BOW methods and identify the more economical approach. Data analysis involves evaluating Bill of Quantity data, understanding project requirements, summarizing BOW and SNI analyses, and collecting price lists for materials, labor, and equipment. The study found that the cost estimation using the SNI 2008 method was Rp 4,312,815,870.00, while the BOW method resulted in Rp 4,990,646,920.00. The SNI 2008 method was 13.58% more economical due to lower coefficient values, especially in reinforcement, concrete work and bricklaying. The research suggests that consultants should use clear, regulation-based methods and conduct thorough cost calculations with appropriate analysis methods to achieve economical and specification-compliant results. Further research is recommended to investigate factors causing project delays and cost impacts.